Work Life Balance Among Female School Teachers Delivering Online Curriculum in Bandgaon Block During Covid - Jayant Kumar Sahoo; Vijay Prakash (International Journal of Integrative Research, 2023)
Work life balance today, in unique in cases of COVID the area home and work place have transgressed boundaries is an integral precursor in order to improve an individual well bring. A enjoyable job well-integrated into life, balances the ordinary mental and emotional quotient of working female mainly in the current pandemic in which the workplace is posing a new and now not like set of challenges and troubles for women. It is turning into stressful when every school and personal life function from the equal space. The predominant thought right here is to apprehend challenges at some factor of COVID which are being confronted with the resource of school teachers in Bandgaon block handing over content to students from home and their surviving strategies. Average literacy rate of Bandgaon Block in 2011 had been 54.46 in which, man and female literacy had been 69.02 and 39.95 respectively. Total literate in Bandgaon Block have been 805 of which man and female have been 547 an 258 respectively. This learn about additionally identifies primary problems and challenges which confronted by using unwedded and wedded working female in the direction of Covid-19. Both Telephonic  and Online interview  are taken to fulfill the objectives. Random sampling approach used to be used for collection of primary data via Telephonic  and Online interviews.